Characterizing soil penetration resistance of planted sago palm (Metroxylon spp.) under mineral soils ecosystem - Wasli, Mohd Effendi; Che Ali, Nurul Hidayah; Yong, Roland; Perumal, Mugunthan; Awang Husaini, Awang Ahmad Sallehin; Kalu, Meekiong; Sim, Siong Fong; Mohamad Jaffar, Aina Nadia Najwa (Sage Publications, 2021)
In-situ soil assessment such as field soil compaction can often be a helpful approach in help determining soil suitability for certain crops. In this study, an assessment was conducted to characterize the Soil Penetration Resistance (SPR) in planted sago palm (Metroxylon spp.) plantation at different growth of rosette and trunking stages under mineral soils ecosystem. SPR in-situ assessment would provide a beneficial guideline and site indicator in determining land suitability before establishing sago plantations, especially on mineral soils. The study was conducted in Mukah, Sarawak, with two study sites at Oya and Talau. The growth stage of sago palm at Oya and Talau site were at the rosette and trunking stage, respectively. The soil types at both study sites consisted of Gley soils (clayey) with significant mineral development at the subsoil horizon. SPR measurements were taken using a Hasegawa-type cone penetrometer. Soil compaction in SSSED Oya was more compact than Talau river research station from shallow depth to subsurface soils. SPR at SSSED Oya ranged between 7.5 to 46.8 J cm-1, while Talau river research station ranged between 1.9 J cm-1 to 11.1 J cm-1. Although there was a significant difference between the growth stage of 0-20 cm and 80-100 cm soils depths, both SSSED Oya and Talau river research station are considered suitable areas for sago palm plantations. Using a practical and convenient approach in assessing soil suitability for sago cultivation, SPR assessment to identify potential areas for the establishment of sago cultivation area can be the fundamental tools for landowners in preparing their land for future cultivation.